SOME ASPECTS OF INTERDEPENDENCE OF SOCIO-ECONOMIC DEVELOPMENT AND MEDICAL-DEMOGRAPHIC SITUATION IN KHERSON REGION - Молікевич, Роман (Human Geography Journal, 2016)
The article discusses the impact of socio-economic development on the formation of medical-demographic situation. The author considered the main socio-economic indicators, by using factor analysis the most significant indicators are identified and the multidimensional evaluation of socio-economic development of administrative units of Kherson oblast was done. The correlation between indicators of socio-economic development and the indicators of medical-demographic situation was calculated. Especially role of urbanization in forming of public health was underlined. Also the spatial features of health systems in Kherson region as one of the indicators of socio-economic development are analyzed.